Standarisasi Kemampuan Membaca dan Menghafal Al-Qur’an Siswa dalam Penilain Munaqosah: Studi Multi-Situs Pada Sekolah Berbasis Agama - Rosikhin, Rifkal Syihabu (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This research aims to explore how SMA Khodijah Surabaya and SMK Baitul Izza Tulungagung design, implement, and evaluate their munaqosah (Qur'anic assessment) programs.Method – Using a qualitative descriptive multi-site study design, data were collected through participant observation, in-depth semi-structured interviews, and document analysis at both institutions. A total of 12 key informants participated in the study. Data analysis followed the Miles, Huberman, and Saldaña framework, employing a two-stage process involving within-site and cross-site analysis. Data validity was ensured through triangulation of sources and methods. Findings – Both schools implement a systematic standardization of Qur'anic assessment based on three core indicators: fluency, tajwid, and fashohah, representing cognitive, psychomotor, and affective learning domains. SMA Khodijah integrates its program with PIQ Singosari Malang through a memorandum of understanding (MoU), with the P3AQ unit responsible for implementation, training, and certification. In contrast, SMK Baitul Izza adopts an autonomous model rooted in its boarding school system, managed by the Tim PPG, with evaluation culminating in a one-month munaqosah at Pondok Wali Barokah Kertosono. Research Implications – The study highlights the practical value of establishing dedicated units for Al-Qur'an assessment development and quality assurance. These models offer adaptable frameworks for broader religious education assessment efforts and provide insights into effective standardization practices. However, a methodological limitation lies in the qualitative approach, which does not allow for statistical examination of variable relationships. Future research is recommended to delve deeper into character and affective dimensions and to map comprehensive quality assurance mechanisms in Qur'anic education.